Erak's ransom - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice, 2011)
On a mission to pay the ransom of a new ally, apprentice Will and the Rangers must first survive the dangerous effects of a desert wasteland.